Atypical Wells syndrome successfully treated with dupilumab - Patrick McMullan; Kristin Torre; Sueheidi Santiago; Gillian Weston; Jun Lu (Wiley, 2023)
Abstract Wells syndrome, also referred to as eosinophilic cellulitis, is a rare and often sporadic inflammatory skin condition whose aetiology remains uncertain. Clinically, this condition presents as a collection of erythematous, oedematous, and tender skin lesions most often affecting the extremities and trunk that can mimic cellulitis. Histologically, Wells syndrome is characterised by inflammatory changes and eosinophilic infiltration of the dermis with the absence of underlying infection, thereby distinguishing it from cellulitis. Due to the rarity of this syndrome and its ambiguous presentation, there remains to be a definitive strategy for treatment. Recent case reports have documented varying success and recurrence with the use of oral and topical corticosteroids, antifungals, antibiotics, immunosuppressants and antihistamines. Here, we report a unique case of progressively worsening neutrophilic‐rich Wells syndrome on the vertex of the scalp that was successfully treated with a combination of dupilumab and oral corticosteroids.